2022
DOI: 10.3390/gels8070433
|View full text |Cite
|
Sign up to set email alerts
|

Gelling Behavior of PAM/Phenolic Crosslinked Gel and Its Profile Control in a Low-Temperature and High-Salinity Reservoir

Abstract: Gel conformance control technology is widely used in moderate and high temperature reservoirs. However, there are few studies on shallow low-temperature and high-salinity reservoirs. The difficulties are that it is difficult to crosslink at low temperatures and with poor stability at high salt concentrations. Therefore, the PHRO gel was developed, which was composed of gelatinizing agent (polyacrylamide), crosslinking agents (hexamethylenetetramine and resorcinol) and crosslinking promoting agent (oxalic acid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…Subsequently, the polymer gel plugs the high permeability layers, significantly decreases the heterogeneity of the reservoir, and increases the sweep coefficient 24 . Conventional polymer gel systems for water shutoff are based on phenolic resin 5,25–27 or chromium crosslinkers 28–30 that can be successfully applied to the low‐temperature reservoirs (≤80°C) and salinities up to ≤50,000 mg/L 4,31 . Meanwhile, for high temperatures (>80°C) and high salinity reservoirs, polymer gels with enhanced thermo‐mechanical stabilities are required 32,33 …”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the polymer gel plugs the high permeability layers, significantly decreases the heterogeneity of the reservoir, and increases the sweep coefficient 24 . Conventional polymer gel systems for water shutoff are based on phenolic resin 5,25–27 or chromium crosslinkers 28–30 that can be successfully applied to the low‐temperature reservoirs (≤80°C) and salinities up to ≤50,000 mg/L 4,31 . Meanwhile, for high temperatures (>80°C) and high salinity reservoirs, polymer gels with enhanced thermo‐mechanical stabilities are required 32,33 …”
Section: Introductionmentioning
confidence: 99%
“…The difference in the rate of vertical conformance and lateral transmission of pressure disturbances leads to a short-term (several months) positive effect on producers (reduction of water-cut, increase in oil rate) [ 5 ]. Examples of conformance control technologies or stimulating the zone closest to wells are the injection of cross-linked polymer agents [ 6 , 7 , 8 ] and sodium-silicate-based gelling agents [ 9 , 10 , 11 , 12 , 13 ], sediment-forming technologies [ 14 ], the use of thermo-gels [ 15 , 16 ] and injection of suspensions [ 17 ], etc. The examples are shown in Figure 1 below.…”
Section: Introductionmentioning
confidence: 99%
“…Yuman Wu et al (2022) [ 31 ] proposed a betaine-based gel used for hydraulic fracturing, it was proved that KCl improves the temperature resistance and increases the viscosity of the optimized fracturing fluid, and the viscoelastic surfactant gel had high shear resistance and high sand-carrying performance. Fei Ding et al (2022) [ 32 ] developed a PHRO gel that was composed of gelatinizing agents, crosslinking agents, and crosslinking promoting agents (oxalic acid). The performance evaluation showed that it has good salt-resistance properties and is suitable for conformance control of low-temperature and high-salinity reservoirs.…”
Section: Introductionmentioning
confidence: 99%